Cost per case or total cost? The potential of prevention of hand injuries in young children - Retrospective and prospective studies - Carlsson Katarina; Ljungberg Elinor M; Dahlin Lars B (BMC, 2008)
Abstract Background Health-care costs for hand and forearm injuries in young children are poorly documented. We examined costs in 533 children injured years 1996-2003. Methods Health-care costs and costs for lost productivity were retrospectively calculated in children from three catchment areas in Sweden. Seven case categories corresponding to alternative prevention strategies were constructed. Results Over time, diminishing number of ward days reduced the health-care cost per case. Among children, the cost of lost productivity due to parental leave was 14 percent of total cost. Fingertip injuries had low median costs but high total costs due to their frequency. Complex injuries by machine or rifle had high costs per case, and despite a low number of cases, total cost was high. Type of injury, surgery and physiotherapy sessions were associated with variations in health-care cost. Low age and ethnic background had a significant effect on number of ward days. Conclusion The costs per hand injury for children were lower compared to adults due to both lower health-care costs and to the fact that parents had comparatively short periods of absence from work. Frequent simple fingertip injuries and rare complex injuries induce high costs for society. Such costs should be related to costs for prevention of these injuries.